MENINGKATKAN KEMAMPUAN BERHITUNG PERMULAAN KELAS I-A DENGAN MENGGUNAKAN METODE PAIKEM (PEMBELAJARAN YANG AKTIF, KREATIF, EFEKTIF, DAN MENYENANGKAN) PADA PELAJARAN MATEMATIKA DI UPT SPF SD NEGERI 060868 MEDAN TIMUR - Hutagalung, Mike Amperawati (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
The purpose of this study was to improve the initial numeracy skills of UPT SPF SD Negeri 060868 Medan Timur, especially grades I-A, so that through the development of early numeracy skills in Indonesian lessons using a quantitative approach using the PAIKEM method. The results of this study are (1) Improving the ability to count beginning in Mathematics Lessons. By using the PAIKEM method in Class I-A UPT SPF SD Negeri 060868 East Medan for the 2019/2020 academic year, this can be seen from the results of observations of the students' initial arithmetic ability to solve math problems, the results obtained from cycle I and cycle II are: 42% and 76% (2) The use of the PAIKEM method in class IA at UPT SPF SD Negeri 060868 Medan Timur for the 2019/2020 lesson can improve early numeracy skills in Mathematics lessons. The increase is evidenced by the results achieved from the activities of doing (answering) the exercises well, based on the observation data of researchers, the results of filling out the initial numeracy indicator instrument. Obtained from 20 students, 2 students completed while 18 students did not complete in cycle I and cycle II of 20 students all completed.